GAMBARAN PEMBERIAN ASUHAN KEPERAWATAN PADA PASIEN KORBAN PASUNG DI RUMAH SAKIT JIWA DAERAH PROVINSI JAMBI - Samsudin Samsudin; Mila Triana Sari (Universitas Baiturrahim, 2017)
Background : Stocks to patients with mental disorders can impact both physically and psychologically. The physical impact could occur atrophy in limbs shackled, namely the psychological impact of trauma patients, revenge to the family, was disposed of inferiority and despair, and long appeared symptoms of depression and suicidal ideation. Method : This research is a quantitative research with a descriptive to find out of nursing care to patients of stocks victims. This is a descriptive quantitative research. The population were 22 nurses who works at Arimbi and Beta room. The number of samples were 19 nurses, and taken by total sampling technique.. Data were collected through questionnaire, and were analyzed through univariate analysis. Result :The findings that is; the assessment was (63.2%), the diagnose was(63.2%), the intervention was (68.4%), the implementation was (63.2%), the evaluation was(52.6%) and the documentation was (52.6%). It is recommended for a mental hospital of Jambi Province that nurses are supported by training, so it is to improve the quality of care delivery in nursing care to patients of stocks victims.